Multi-Dimensional Display of Wang’s Lymph Node Map Using Virtual Bronchoscopic Navigation System - Lan, Fen; Yue, Yaling; Shen, Hong; Shen, Hui; Wang, Qiyuan; Yu, Xiujing; Chen, Laijuan; Li, Qin; Wang, Kopen; Liu, Qinghua; Xia, Yang (Frontiers in Molecular Biosciences, 2021)
Background: Transbronchial needle aspiration (TBNA) is a classical technique for diagnosing mediastinal-hilar lymph node enlargement. However, the diagnostic value of conventional TBNA (cTBNA) is limited in small lymph nodes. Methods: Here, we generated an innovative multi-dimensional virtual lymph node map on top of Wang’s lymph node map using a Lungpoint Virtual Bronchoscopic Navigation System. Results: The virtual bronchoscopic navigation (VBN) system was combined with computed tomography (CT) images to generate extrabronchial, endobronchial, sagittal, coronal as well as horizontal views of the 11 intrathoracic lymph node stations and their adjacent tissues and blood vessels. We displayed the specific puncture site of each lymph node station. The 11 stations were divided into four groups: right mediastinal stations, left mediastinal stations, central mediastinal stations and hilar stations. Conclusion: The VBN system provides a precise view of the intrabronchial landmarks, which may increase the diagnostic accuracy of intrathoracic lymph node adenopathy and assist bronchoscopists with practicing TBNA.